Comparative analysis of sour cherry cultivars on their ecological and biological indicators - Surányi, D. (International Journal of Horticultural Science, 2021)
Sour cherries developed in the northern hemisphere, an alloploid hybrid of dwarf sour cherries (Prunus fruticosa) and bird cherries (P. avium), born in the confluence of the two species. However, the ecological and, above all, cold tolerance of the ancestor of cultivated sour cherries is higher than that of wild cherries (De Candolle, 1894; Rehder, 1954; Terpó, 1974; Iezzoni et al., 1991; Faust & Surányi, 1997). The cultivation limits are in the northern hemisphere 38-44. degree. The Carpathian Basin, the Balkans and Asia Minor are considered to be the main birthplaces for sour cherries. The genetic and morphological diversity of sour cherries is greater than that of the basic species (Iezzoni et al. 1991; Faust & Surányi, 1997). In the study, 472 sour cherry cultivars were compared based on 7 relative ecological indicators and 3 biological values. Compared to other Prunus species, we mostly found less variability in sour cherries - not counting their salt tolerance (SB). The partial similarity between open pollination (OP), frost tolerance (FR) and disease resistance (DR) - partly true in terms of varieties, but also reflected the effects of purposeful breeding and selection. The cultivars together - in comparison, showed balance, but in the highlighting, the differences of the 3 cultivar groups became significant. Indeed, the differences between the species of the former Hungarian cultural flora are clearly different (Surányi, 2004), which is also the case when comparing a large number of apricot (Surányi, 2014), plum (Surányi, 2015) and peach (Surányi, 2020) varieties.